Entrepreneurship and the business cycle - Roy Thurik (IZA World of Labor, 2014)
Entrepreneurship has a cyclical component, raising two questions. Is the entrepreneurship cycle related to the business cycle? And is there causality? A two-way relationship between entrepreneurship and the business cycle would be in line with the two faces of entrepreneurs: as agents of change creating upswings (opportunity entrepreneurship) and as rational actors escaping unemployment by setting up a business (necessity entrepreneurship). Nascent entrepreneurship can indeed be precyclical, implying that the two faces of entrepreneurship also show up in the business cycle, with promising policy implications.
Keywords: E32; L26; 330; entrepreneurship; business cycle; precyclicality; nascent entrepreneurship